2017
DOI: 10.1063/1.4995513
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoplatelets: Thermal diffusivity and thermal conductivity by the flash method

Abstract: The present work deals with the measurement of thermo-physical properties of a freestanding sheet of graphene (thermal diffusivity and thermal conductivity), and their dependence on sample density as result of uniform mechanical compression. Thermal diffusivity of graphene nano-platelets (thin slabs) was measured by the pulse flash method. Obtained response data were processed with a specifically developed least square data processing algorithm. GNP specific heat was assumed from literature and thermal conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Higher wickability of the coatings allows a continuous liquid supply to the nucleation cavities during boiling, thereby delaying the vapor layer formation and enhancing the critical heat flux of the coatings. Several reports 38 40 have shown that thermal conductivity of a few layered graphene (2–4 layers) is in the range of ~ 2,300 W/m K to ~ 3,000 W/m K (as against 3,000 W/m K to 5,000 W/m K for a single layer of graphene). And reduces to ~ 2000 W/m K with increase in the number of deposited graphene layers (greater than 4 layers).…”
Section: Resultsmentioning
confidence: 99%
“…Higher wickability of the coatings allows a continuous liquid supply to the nucleation cavities during boiling, thereby delaying the vapor layer formation and enhancing the critical heat flux of the coatings. Several reports 38 40 have shown that thermal conductivity of a few layered graphene (2–4 layers) is in the range of ~ 2,300 W/m K to ~ 3,000 W/m K (as against 3,000 W/m K to 5,000 W/m K for a single layer of graphene). And reduces to ~ 2000 W/m K with increase in the number of deposited graphene layers (greater than 4 layers).…”
Section: Resultsmentioning
confidence: 99%
“…In [6] a better description of the real flash signal was adopted, approximating the pulse with two overlapping exponentials, each with its own time constant:Sfalse(τfalse)=A[expfalse(R1τfalse)expfalse(R2τfalse)] where A represents the signal intensity connected with the supplied energy, while R 1 , and R 2 are the inverses of the two time constants, the first linked to the lamp filament temperature increase, and the second to the time constant of the flash capacitor discharge. The way to determine R 1 and R 2 is described in [6].…”
Section: Analytical Solutionmentioning
confidence: 99%
“…Using Equation (2) as input, in the way described by the Green function method [16], the solution is as follows (see Appendix A of [6]):Tfalse(L,τfalse)=A{1exp(R1τ)R1exp(R2τ)1R2+2truen=1[false(1false)n×(exp(R1τ)exp((nπL)2ατ)(nπL)2αR1exp(R2τ)exp((nπL)2ατ)(nπL)2αR…”
Section: Analytical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-temperature diffusivity , defined by the thermal conductivity [W/(m·K)], mass density [kg/m ] and specific heat capacity [J/(kg·K)], is a necessary trait for optimised polymeric materials and their composites. As graphene has a very high in-plane 3000 W/(m·K) conductivity, it is a potential filler in polymeric and epoxy hosts for increased thermal and electrical conductivity; the out-of-plane conductivity of graphene-stack is only 5 W/(m·K) [ 4 ]. Composites that use graphene as the filler, it was previously shown that the thermal conductivity is increasing linearly with its weight percentage (up to 30 wt% before saturation), and in the case of NC-paper with 10 wt% of graphene, reached high 25 W/(m·K) values [ 5 ].…”
Section: Introductionmentioning
confidence: 99%